Paper #3 – Conflict Theory - Brubaker, Sarah Jane (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Write a paper addressing one of the following topics: 1. Making reference to Marx’s ideas, concepts and theories, describe your experience as a worker. 2. Describe the Marxian concept of alienation (give examples of each component). What does he mean by "species-being," and how is this related to alienation? 3. Identify and define Weber’s 4 rationality types.